MOTHER'S KNOWLEDGE ABOUT TEETH ERUPTION WITH CLOCK TEETH IN ELEMENTARY STUDENTS - Reca; Teuku Salfiyadi; Cut Aja Nuraskin; Mufizarni (Jurnal Ilmiah Keperawatan, 2023)
Dental and oral problems in children need attention from parents. Entering school age, the child's permanent teeth begin to grow so that in the child's oral cavity there is mixed dentition. This study aims to determine the relationship between mother's knowledge about the changing period of teeth with crowding In Class V Students Kayee Leue SDN, Aceh Besar District.This research is analytic with a cross sectional approach. Sampling used total sampling, namely all In Class V Students Kayee Leue SDN, totaling 56 students and their mothers as respondents, by conducting dental examinations on children and interviews with mothers. The research instrument used a diagnostic set and a questionnaire. The results of the study were tested statistically using the SPSS program with a chi-square test (a = 0.05). The results showed There is a relationship between mother's knowledge about the change of teeth with crowding In Class V Students Kayee Leue SDN (p value = 0.0001). Conclusion The understanding of Mother's knowledge about the changing period of teeth has a significant relationship with crowding In Class V Students Kayee Leue SDN.